2018
DOI: 10.1037/emo0000337
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting reactive and proactive control of emotional distraction.

Abstract: Attending to emotional stimuli is often beneficial, because they provide important social and environmental cues. Sometimes, however, current goals require that we ignore them.To what extent can we control emotional distraction? Here we show that the ability to ignore emotional distractions depends on the type of cognitive control that is engaged.Participants completed a simple perceptual task at fixation while irrelevant images appeared peripherally. In two experiments, we manipulated the proportion of trials… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(98 citation statements)
references
References 73 publications
12
86
0
Order By: Relevance
“…However, the current findings add to a growing body of evidence with faces (Fox et al, 2000;Fox, Russo, Bowles, & Dutton, 2001;Horstmann et al, 2012;Horstmann & Becker, 2008;Nummenmaa & Calvo, 2015), words (Calvo & Eysenck, 2008;Georgiou et al, 2005), fearrelated stimuli Soares, Esteves, & Flykt, 2009;Vromen, Lipp, & Remington, 2015), or complex scenes (Grimshaw, Kranz, Carmel, Moody, & Devue, 2017;Lichtenstein-Vidne, Henik, & Safadi, 2012;Maddock, Harper, Carmel, & Grimshaw, 2017;Okon-Singer, Tzelgov, & Henik, 2007), showing that the emotional value of a stimulus does not affect early selection processes in a purely bottom-up fashion. These studies all suggest that the processing of emotional information is not automatic but depends on the availability of attentional resources, and is partly guided by top-down components such as expectation, motivation, or goal-relevance.…”
Section: Discussionmentioning
confidence: 91%
“…However, the current findings add to a growing body of evidence with faces (Fox et al, 2000;Fox, Russo, Bowles, & Dutton, 2001;Horstmann et al, 2012;Horstmann & Becker, 2008;Nummenmaa & Calvo, 2015), words (Calvo & Eysenck, 2008;Georgiou et al, 2005), fearrelated stimuli Soares, Esteves, & Flykt, 2009;Vromen, Lipp, & Remington, 2015), or complex scenes (Grimshaw, Kranz, Carmel, Moody, & Devue, 2017;Lichtenstein-Vidne, Henik, & Safadi, 2012;Maddock, Harper, Carmel, & Grimshaw, 2017;Okon-Singer, Tzelgov, & Henik, 2007), showing that the emotional value of a stimulus does not affect early selection processes in a purely bottom-up fashion. These studies all suggest that the processing of emotional information is not automatic but depends on the availability of attentional resources, and is partly guided by top-down components such as expectation, motivation, or goal-relevance.…”
Section: Discussionmentioning
confidence: 91%
“…Our question concerns the effects of lateralisation of the emotional stimuli on response inhibition processes. Importantly, emotional information can be extracted from peripherally-presented complex scenes, even with very brief stimulus presentations [52,53]. We therefore determined whether emotion affected either behavioural or electrophysiological measures of the response inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the sample size needed to detect an effect of reward on emotional distraction, we used the effect size (d s = .84) from Grimshaw et al (2017), using distractor-frequency (25% vs. 75%) as a proxy for the potential effect of reward on emotional distraction (RTintact -RT-scrambled, collapsed across positive and negative). At 90% power (α=.05), this yielded 26 participants per group.…”
Section: Sample Size Determinationmentioning
confidence: 99%
“…Biologically-relevant, high arousal, positive images can attract attention just as powerfully as negative images (Grimshaw, Kranz, Carmel, Moody, & Devue, 2017;Gupta, Hur, & Lavie, 2016;Most, Smith, Cooter, Levy, & Zald, 2007), and in some contexts they can be even more difficult to ignore. For example, using a letter-search task with centrallypresented task-irrelevant emotional images, Gupta and colleagues (2016) found that increasing the task's perceptual load eliminates distraction from negative but not positive images.…”
mentioning
confidence: 99%
See 1 more Smart Citation